Bubu Sebagai Alat Tradisional Penangkap Ikan Yang Efektif dan Ekonomis Bagi Nelayan - Afriyansih, Silvi; Adibrata, Sudirman; Mufiadi, M. Rizza; Andriyansah, Andriyansah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Bubu is a non-selective fishing gear that the types of fish caught were varied, especially demersal. From several fishing gears, bubu are high economic value so that the demand for fishery resource products is increased by it. The purpose of this study was to determine the construction of fishing gear, composition, and effectiveness of fish caught using bubu. This research conducted in March-April 2022 at Tanjungpandan Nusantara Fishery Port (PPN) Belitung Regency. Descriptive analysis used in this method by interviewes with fisherman who used bubu. Determination the number of respondents using the census method with total number interviewed as many as 46 fisherman. Methods to determine the effectiveness of bubu fishing can be seen from the type of main catch, production per trip, fishing area, and gear construction. The results obtained from this study are that the bubu has a fishing gear construction consisting of a body frame using wood and rattan, mouth frame using wire height with of 100-155 cm, lenght of 60-165 cm, width of 20-85 cm and has an outer mouth diameter of 30-50cm, mouth width of 10-25 cm, while the inside diameter of mouth is 20 cm with mesh size of 3 cm. There are 14 types of fish caught in the bubu, such us Siganus guttatus, Gnathanodon speciosus, Lethrinus letjan, Epinephelus fuscoguttatus, Abalites stellatus, Lutjanus vittus, Caesio cuning, scarus ghoban, Epinephelus areolatus, Diagrama pictum, Lutjanus erythropterus, Plectropanus leoparius, Sphyaerana baraccuda, Carangoides plagiotaenia. The composition of main catch catch is 99.75%, by catch 0.25%. The effectiveness of trap fishing gear gets a score of 80%. So that the use of traps has been effective for use